(untitled) (Modern education and development, 2024)
This article explores the metaphorization of tongue twisters in both English and Uzbek languages. It highlights how metaphors embedded in tongue twisters go beyond phonetic challenges, reflecting cultural values, natural elements, and social experiences. By analyzing examples from both linguistic traditions, the article reveals how metaphorical imagery enhances the meaning and purpose of tongue twisters, turning them into both educational tools and cultural symbols. The study emphasizes the role of metaphors in connecting linguistic practices with broader cultural understandings.